Sentimental analysis on political speeches - Atiq, Asif; Abeed, Abrar Shahriar; Efat, Azher Ahmed; Momin, Armanul (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.